Basic Body Awareness Therapy versus standard care in hip osteoarthritis. A randomized controlled trial. (22nd November 2021) - Olsen, Aarid Liland; Magnussen, Liv Heide; Skjaerven, Liv Helvik; Assmus, Jörg; Sundal, Mary‐Anne; Furnes, Ove; Hallan, Geir; Strand, Liv Inger
Abstract: Background: Compensational movement patterns in hip osteoarthritis (HOA) are associated with hip dysfunction. Basic Body Awareness Therapy (BBAT) promotes functional movement quality and might, accordingly, be beneficial in HOA. Objective: To examine the outcomes of BBAT compared to standard care in people with HOA after first receiving patient education (PE). Study Design: A prospective, assessor‐blinded, and block‐randomized controlled trial. Methods: Community‐living adults with HOA participating in PE were randomly allocated to an intervention group receiving BBAT in groups (12 sessions offered once a week), or a comparison group. Data at baseline (pretest) and at 6 months (posttest) were analyzed. Primary outcomes were pain during walking assessed by the Numeric Rating Scale (NRS) and function by the Hip Osteoarthritis Outcome Score, subscale ADL (HOOS A). Secondary outcomes addressed physical capacity, movement quality, and self‐reported aspects of function and health. Results: At pretest, there were no significant differences in demographic and test data between the intervention ( n  = 51) and the comparison ( n  = 50) group. Forty‐one intervention and 45 comparison participants completed the posttest. At posttest, no significant differences in change between groups were found on NRS ( p  = 0.694, effect size (ES) = 0.02) or HOOS A ( p  = 0.783, ES = 0.07). Among secondary outcomes, movement quality improved significantly more ( p  < 0.001, ES = 0.84) in the intervention group. Compliance with BBAT varied substantially. Per‐protocol analysis showed changes in favor of the intervention group for self‐efficacy ( p  = 0.049, ES = 0.36), health ( p  = 0.037, ES = 0.44), and function ( p  = 0.029, ES = 0.53) when only intervention participants who completed at least 10 sessions of BBAT were included. Conclusions: BBAT was not found to be a more effective treatment modality than self‐initiated standard care to reduce pain during walking and improve daily functioning in people with HOA. Movement quality was significantly more improved in participants receiving BBAT, and improvement in other health aspects was associated with sufficient therapy compliance.